Identification of Suitable Plant Species for Vegetation Restoration at Manthali, Nepal - Poudel, Sunita; Chettri, Mukesh Kumar (Amrit Research Journal, 2021)
The present study aims to find out the suitable native plant species for restoring degraded land in the mountain from 450 m asl to 819 m asl in Khurkot of Manthali. Altogether thirty quadrats were laid to observe frequency, density and coverage of plant species present there, and ultimately, IVI was calculated. Eight plant species – 3 trees like Acacia catechu, Aegle marmelos and Annona squamosa; 3  shrubs like Rhus parviflora, Cipadessa baccifera and Abrus precatorius (woody climber), and 2 herbs like Uraria lagopodiodes and  Polypogon monospeliensis were considered for the detailed study based on their high IVI values. Altogether fourteen traits (growth  form, life-span, phenology, Raunkiaer’s life-form, canopy height, stem density, mean ramet distance, leaf size, specific leaf area, leaf  thickness, seed mass, propagules mass, seed shape and nitrogen fixation) were studied in those eight species. Based on these traits,  through this protocol, the plants were again categorized into five syndromes, i.e., establishment syndrome, dispersal syndrome,  biomass producing syndrome, persistence syndrome and effect on environment syndrome. From this study, Annona squamosa and  Abrus precatorius can be suggested as candidate species for early succession. Similarly, Aegle marmelos, Acacia catechu, Annona  squamosa, Rhus parviflora and Abrus precatorius can be recommended to plant for restoration of degraded bushy lands, which are in  the phase of secondary succession.